Characterization of Silk Fibroin/Hyaluronic Acid Blend Films Cross-linked with EDC (Journal of Fiber Bioengineering and Informatics, 2018)
Silk fibroin (SF) / hyaluronic acid (HA) blend films were prepared using 1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) as crosslinking agent and N-hydroxysuccinimide (NHS), 2-morpholinoethanesulfonic acid (MES) as assistant agents. The physico-chemical properties of the blend films were examined and analyzed. The FTIR shows that HA interferes with SF to form crystal structures, whereas EDC induces SF to form Silk I. Compared to the uncross-linked blend films, the EDC cross-linked blend films show an obvious increase in elongation at break, and a decrease in tensile strength and Young's modulus. The flexibility of the films improved significantly. L929 cells grew well on SF/HA blend films, demonstrating that the blend films cross-linked with EDC have no significant toxicity.